Le modèle de double régulation de l’activité : un modèle-guide pour la formation en ergonomie à l’Université - Muriel Prévot-Carpentier; Cathy Toupin (Perspectives Interdisciplinaires sur le Travail et la Santé)
The double regulation model, also known as the five-square model proposed by Leplat and Cuny in 1977, remains central to activity analysis in ergonomics as it constitutes an open framework and a matrix for understanding activity in real-world situations. This model, based on a systemic approach, defines the main categories of variables and relationships through which any activity can be characterized. More specifically, it aims to identify the determinants that shape and influence activity, as well as its effects on the individual being observed and the surrounding system. This article seeks to trace the emergence of this activity modeling in Jacques Leplat's work, explain the key principles of the model, and illustrate its essential role as a guiding tool for ergonomics training at the university level, using a case study conducted in the hospital sector.